The Performative Failure of the “Great Russia” Narrative: A Speech Act Analysis and the Transformation of Ukrainian National Identity - Nabilah Najwa (Pustaka Digital Indonesia, 2026)
This study is urgent because it reveals how the performative failure of the “Great Russia” narrative, rather than legitimizing domination, has unintentionally accelerated the consolidation and transformation of Ukrainian national identity, challenging prevailing assumptions about the power of hegemonic discourse in international politics. The Russia Ukraine conflict reflects not only a territorial dispute, but also a war of meaning through language and historical narratives. President Vladimir Putin often uses the narrative of ‘Greater Russia’ as a basis for political legitimacy to justify aggression against Ukraine. This narrative represents a form of speech act that aims to create a new political reality in which Ukraine is considered part of a larger Russian identity. However, the phenomenon that occurs is paradoxical: instead of strengthening Russia's cultural claims, the narrative fails performatively and triggers the consolidation of Ukrainian national identity. This study employs a qualitative-descriptive research design aimed at explaining why Russia’s “Greater Russia” narrative failed performatively and how it paradoxically strengthened Ukrainian national identity. This study aims to analyse the failure of Russian linguistic actions using a descriptive qualitative approach with the analytical tool of Speech Act theory from the Copenhagen School. Data was obtained from secondary sources such as official speeches, public opinion surveys (Pew Research, KIIS), and academic literature related to changes in Ukraine's national identity after 2014. The results of the study show that the failure of Russian political discourse was caused by changes in Ukraine's socio-political context, which eliminated Moscow's symbolic legitimacy. The ‘Greater Russia’ narrative lost its effectiveness because the intended audience rejected the constructed meaning, so that the political discourse no longer had performative power. This study confirms that in contemporary global politics, linguistic power cannot stand without audience recognition. Language, in the context of modern conflict, has become the main arena where legitimacy and identity are negotiated.